Iodination and chlorination of aromatic polycyclic hydrocarbons with iodine monochloride in aqueous sulfuric acid; Russian Journal of Organic Chemistry; Vol. 37, iss. 8 - Chaikovskii V. K. Vitold Kazimirovich (2001, 2001)
Title screen